Fazlur Rahman's Ethical-Transformative Neo-Sufism: The Reactualization of Islamic Spirituality for the Crisis of Modernity: Neo-Sufisme Etis-Transformatif Fazlur Rahman: Reaktualisasi Spiritualitas Islam untuk Krisis Modernitas - Muhammad Sakdullah; Thiyas Tono Taufiq; Djurban Djurban; Wawaysadhya Wawaysadhya (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2026)
This study aims to analyze Fazlur Rahman’s neo-Sufism as an ethical-transformative paradigm of contemporary Islamic spirituality. This topic is important because modern society faces spiritual and moral crises marked by materialism, alienation, anxiety, and the weakening of social responsibility. This research uses a qualitative library-based method by examining Rahman’s major works, especially Islam, Islam and Modernity, Islamic Methodology in History, and Islamic Modernism: Its Scope, Method and Alternatives. Data were collected through documentation and analyzed using qualitative content analysis with a hermeneutical-contextual approach. The findings show that Rahman’s neo-Sufism reorients Sufism from individual asceticism toward social ethics. Through his double movement hermeneutics, Sufi values such as sincerity, ascetic restraint, patience, trust in God, and purification of the soul are reinterpreted as moral principles relevant to modern life. These values do not only function as instruments of inner purification but also as foundations for self-control, moral integrity, social responsibility, and public ethics. The study implies that Rahman’s neo-Sufism can contribute to the development of Sufi psychotherapy, Islamic counseling, religious moderation, and Islamic social ethics. The originality of this study lies in its formulation of Rahman’s neo-Sufism as an integrative framework that connects inner spirituality, moral hermeneutics, psychological healing, and social transformation.